Effect of economic vulnerability on competitive advantages, enterprise performance and sustainability - Al Mamun, Abdullah; Che Nawi, Noorshella; Ibrahim, Mohd Asrul Hery; Muniady, Rajennd (2018)
This study investigated the effect of economic vulnerability upon competitive advantages, performance, and sustainability of micro-enterprises owned and managed by micro-entrepreneurs who participate in varied development initiatives in Peninsular Malaysia. Upon adopting the cross-sectional design, data were randomly collected from selected 300 micro-entrepreneurs from the eKasih program (national poverty data bank) located in four states of Peninsular Malaysia. The quantitative data were collected by conducting structured interview sessions with the respondents held from September until November 2017. The findings revealed that the state of economic vulnerability among the respondents had a significantly negative effect on the aspects of competitive advantages, performance, and sustainability among micro-enterprises in Peninsular Malaysia. Despite of the widely acknowledged and empirically examined effects of socioeconomic antecedents upon micro-enterprise performance, the focus on the effect of a more comprehensive measure of socioeconomic condition, that is, economic vulnerability, among low-income households appears to be scant. Hence, the outcomes of this study are able to provide critical insights for development organizations pertaining to development programs and their effectiveness on economically vulnerable, particularly among low-income households in Peninsular Malaysia.